2020
DOI: 10.17220/ijpes.2020.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Participation in Physical Activity and Social Media Addiction in Students

Abstract: The purpose of this research was to examine participation in physical activity and social media addiction among university students. A total of 462 university students from 3 different universities voluntarily participated in the study. In the study, the "Motivation Scale for Participation in Physical Activity" and "Facebook addiction scale" were used as data collection tools. In the study, the independent sample t-test and One-way ANOVA test were applied for normally distributed data depending on the number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…In addition, this study found that there is no association between sociodemographic background which are gender, age, year of study and CGPA with the level of social media addiction among the participants (with p-value less than 0.05. Some studies supported the findings in which social media addiction did not differ in term of gender (22) (23) and a study from Malaysia revealed that Facebook addiction is not affected by the gender since the ratio of addiction among males and females are approximately similar (24). However, other studies discovered that the mean score for the social media or internet addiction is significantly higher in male compared to female and inversely (25) (26).…”
Section: Discussionmentioning
confidence: 58%
“…In addition, this study found that there is no association between sociodemographic background which are gender, age, year of study and CGPA with the level of social media addiction among the participants (with p-value less than 0.05. Some studies supported the findings in which social media addiction did not differ in term of gender (22) (23) and a study from Malaysia revealed that Facebook addiction is not affected by the gender since the ratio of addiction among males and females are approximately similar (24). However, other studies discovered that the mean score for the social media or internet addiction is significantly higher in male compared to female and inversely (25) (26).…”
Section: Discussionmentioning
confidence: 58%
“…Hypothesis 4 (H4): Social media addiction increases physical health issues. Past research has revealed that uncontrollable usage of social media has an effect on physical and mental health, such as cardio-metabolic health, sleep, affect, self-esteem, wellbeing and functioning, particularly in adolescents [31]. Hypothesis 5 (H5): Social media usage hours increase physical health issues.…”
Section: Hypothesesmentioning
confidence: 99%
“…A prior study also showed that problematic smartphone use is linked to physical inactivity during this COVID-19 outbreak [31] and that these trends in smartphone use may increase [31]/decrease [32] the use of Facebook, which turns into an addiction. Other studies also revealed that the increase in physical activities reduces/increase Facebook addiction [14,32,33]. As an adaptation measure to personal and work life, COVID-19-induced lockdown resulted in people becoming more attached to their smartphones [34,35], and such problematic use may lead them to use their smartphones and social media sites even during any type of physical activity like a workout.…”
Section: Plos Onementioning
confidence: 99%